High Oleic Acid Peanut Oil and Extra Virgin Olive Oil Supplementation Attenuate Metabolic Syndrome in Rats by Modulating the Gut Microbiota - Zhao, Zhihao; Shi, Aimin; Wang, Qiang; Zhou, Jinrong (Nutrients, 2019)
Unhealthy dietary patterns are important risk factors for metabolic syndrome (MS), which is associated with gut microbiota disorder. High oleic acid peanut oil (HOPO) and extra virgin olive oil (EVOO), considered as healthy dietary oil, are rich in oleic acid and bioactive phytochemicals, yet efficacy of MS prevention and mechanisms linking to gut microbiota remain obscure. Herein, we investigated HOPO and EVOO supplementation in attenuating diet-induced MS, and the potential mechanisms focusing on modulation of gut microbiota. Physiological, histological and biochemical parameters and gut microbiota profiles were compared among four groups fed respectively with the following diets for 12 weeks: normal chow diet with ordinary drinking water, high-fat diet with fructose drinking water, HOPO diet with fructose drinking water, and EVOO diet with fructose drinking water. HOPO or EVOO supplementation exhibit significant lower body weight gain, homeostasis model assessment-insulin resistance (HOMA-IR), and reduced liver steatosis. HOPO significantly reduced cholesterol (TC), triglyceride (TG), and low-density lipoprotein (LDL) level, while EVOO reduced these levels without significant difference. HOPO and EVOO prevented gut disorder and significantly increased β-diversity and abundance of Bifidobacterium. Moreover, HOPO significantly decreased abundance of Lachnospiraceae and Blautia. These findings suggest that both HOPO and EVOO can attenuate diet-induced MS, associated with modulating gut microbiota.